Recalcitrance of hair in historical plasters. (November 2020) - Tintner, J.; Rennhofer, H.; Kennedy, C.J.; Revie, W.A.; Weber, H.; Pavlik, C.; Lanszki, J.
Highlights: Historical hair in plasters does not age continuously over time. Grinding leads to significant changes in infrared spectra. Small angle X-ray Scattering revealed certain grouping according to age. Historical hair and recent hair leads to comparable infrared spectra. Infrared spectra of different animal species mirror chemical differences. Abstract: Hair amendments were extracted from the lime plasters of historical buildings with an age ranging from recent times until the 12 th century. Infrared spectroscopy has been used to assess chemical changes, small-angle X-ray scattering (SAXS) for changes of the physical structure. As a reference a sample set of 130 recent samples has been collected comprising different species. The only strong impact on hair chemistry was detected for grinding the samples. This pretreatment separated the chemical fingerprint based on methylene bands (2920 and 2850 cm −1 ) and the CO vibration band at 1740 cm −1 . Different species were separated only on a coarse level. Historical samples did not display very clear indicators of aging processes. SAXS results registered a certain grouping of the samples according to age. A clear trend was not found, however. This suggests that age alone is not the key defining factor in the degradation processes in hair.